Social deprivation and premature mortality: regional comparison across England. Issue 6912 (30th October 1993) - Eames, M; Ben-Shlomo, Y; Marmot, M G
Abstract : OBJECTIVE--To investigate the pattern and size of the relationship between social deprivation in electoral wards and premature mortality for each health region in England. DESIGN--Ecological study using 1981 census variables and data on mortality for 1981-5. SETTING--14 regional health authorities in England. MAIN OUTCOME MEASURE--Mortality under the age of 65 years from all causes, coronary heart disease, and smoking related diseases in men and women. RESULTS--Increasing deprivation was significantly associated with mortality from all causes, coronary heart disease, and smoking related diseases. The relationship was linear with no apparent threshold. Correlation coefficients were generally greater for deaths from all causes and smoking related diseases and for men compared with women. The slope of the relationship between deprivation and mortality varied among regions. Variations in mortality still existed between regions for equal levels of deprivation. CONCLUSION--Deprivation of an area and premature mortality are strongly linked. The effects of deprivation can be seen throughout the range of affluence and are not limited to the poorest areas. Current targets for reducing coronary heart disease mortality may be achievable if the mortality in poor areas can be reduced to the rates in affluent areas.